2009
DOI: 10.1002/pen.21319
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of air plasma treated poly vinylidene fluoride and poly methyl methacrylate films

Abstract: In this investigation, the surface modification of poly vinylidene fluoride (PVDF) and poly methyl methacrylate (PMMA) film induced by air plasma has been investigated using contact angle measurement, electron spectroscopy for chemical analysis (ESCA), and ATR‐FTIR spectroscopy. Plasma treatment affects the polymer surfaces to an extent of several hundreds to several thousand angstroms deep, and the bulk properties of the polymer substrate are never modified because of its low penetration range. Plasma surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 51 publications
1
26
3
Order By: Relevance
“…In contrast, the surface energy has increased from 49.59 ± 0.02 mJ/m 2 for the PVA/PVP blend film to 57.97 ± 0.03 mJ/m 2 for the nanocomposite film with 25 wt % SiO 2 content, which indicates enhanced wettability in the nanocomposite films compared to the PVA/PVP blend film. The contact angle values were used to calculate the work of adhesion using the formula given in our previous report . It was found that the work of adhesion also increased from 111.08 mJ/m 2 for the PVA/PVP blend film to 124.97 mJ/m 2 for the nanocomposite film with 25 wt % SiO 2 content.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the surface energy has increased from 49.59 ± 0.02 mJ/m 2 for the PVA/PVP blend film to 57.97 ± 0.03 mJ/m 2 for the nanocomposite film with 25 wt % SiO 2 content, which indicates enhanced wettability in the nanocomposite films compared to the PVA/PVP blend film. The contact angle values were used to calculate the work of adhesion using the formula given in our previous report . It was found that the work of adhesion also increased from 111.08 mJ/m 2 for the PVA/PVP blend film to 124.97 mJ/m 2 for the nanocomposite film with 25 wt % SiO 2 content.…”
Section: Resultsmentioning
confidence: 97%
“…The contact angle values were used to calculate the work of adhesion using the formula given in our previous report. 45 It was found that the work of adhesion also increased from 111.08 mJ/m 2 for the PVA/PVP blend film to 124.97 mJ/ m 2 for the nanocomposite film with 25 wt % SiO 2 content. Thus, the contact angle analysis reveals a notable change in the surface characteristics of PVA/PVP/SiO 2 nanocomposite films with an increase in the SiO 2 content.…”
Section: Wettability Studiesmentioning
confidence: 99%
“…The signal corresponding to F being higher on the nonmodified fibers than in plasma modified fibers plasma treatment leads to a substantial decrease on fluorine content and an increases in oxygen content as a result of the presence of carboxyl groups in the surface of the fibers generated by the O 2 plasma treatment. [33] The oxygen to carbon ratio (O/C) increases from 0.007 to approximately 0.1 while fluorine to carbon ratio (F/C) decreases from 0.54 to approximately 0.21.…”
Section: Chemical Composition Of Electrospun Pvdf Fibers Surfacementioning
confidence: 99%
“…Also, the peak at 3007 cm -1 could be assigned to aromatic C-H stretching vibrations of Several peaks of PMMA were observed in the FTIR spectra of composites. The bands at 2931 cm -1 is attributed to the CH 2 stretching vibrations [30,31] and the bands at 1733 and 1433 cm -1 are due to the stretching vibrations of C=O and -O-CH 3 groups of PMMA. The band at 1438 cm -1 is assigned to CH 2 scissoring and the bands at 1255 cm -1 are assigned to the C-O stretching vibration of PMMA.…”
Section: Ftir Spectroscopymentioning
confidence: 98%